2009
DOI: 10.3171/2009.1.spine08718
|View full text |Cite
|
Sign up to set email alerts
|

Clinical prognostic indicators of surgical outcome in cervical spondylotic myelopathy

Abstract: Object The objective of this systematic review was to use evidence-based medicine to assess whether clinical factors predict surgical outcomes in patients undergoing cervical surgery. Methods The National Library of Medicine and Cochrane Database were queried using MeSH headings and keywords relevant to clinical preoperative factors. Abstracts were reviewed, and studies that met the inclusion criteria we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(73 citation statements)
references
References 19 publications
4
67
0
2
Order By: Relevance
“…3 We found that pre-surgical CMCT at the lower limbs can predict functional recovery. Thus, our work further supports this view 5 and refutes studies with opposite findings.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…3 We found that pre-surgical CMCT at the lower limbs can predict functional recovery. Thus, our work further supports this view 5 and refutes studies with opposite findings.…”
Section: Discussionmentioning
confidence: 98%
“…1- 3 We compared TMS and MRI findings between a group of patients who underwent surgery for cervical spondylotic myelopathy and a second group with spondylosis, who were not operated upon, and we correlated these abnormalities with longitudinal clinical follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some surgeons would suggest early surgery for patients with CSM to ameliorate the risk of SCI. 2,9,19,21,22,24,27,33 However, there are insufficient data to correlate CSM with SCI, and whether the risk of SCI can be altered by surgical intervention remains elusive.…”
mentioning
confidence: 99%
“…In a complementary article, Holly et al 6 efficiently summarized our current knowledge of the clinical prognostic indicators of surgical outcomes in CSM. There is consistent Class III evidence that the duration of symptoms, and possibly advancing age, negatively affect outcome.…”
Section: Cervical Spondylotic Myelopathymentioning
confidence: 99%
“…Holly et al, 6 in their excellent summary of the clinical prognostic indicators of surgical outcomes in CSM, showed that there is Class II evidence that somatosensory evoked potentials, and in particular recordings obtained following stimulation of the median nerve, have prognostic power. The use of EMGs has not been convincingly shown to be predictive of recovery in either myelopathy or radiculopathy, and there is conflicting Class III evidence regarding its predictive power (see the article by Mummaneni et al 15 in this issue).…”
Section: Predictive Value Of Electrophysiology and Imaging In Csmmentioning
confidence: 99%